Pattern of prescription and drug use in psychiatry out patient department of private practitioners of Central India - Shamkuwar, Chetna A.; Chakravorty, Ashish D.; Shrivastava, Meena P.; Deshmukh, Ragini (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Psychotropic drugs have had a remarkable impact in psychiatric practice. The continuous monitoring of prescription and drug utilization studies may help to identify the problem involved in therapeutic decision and promote rational prescribing. Very few studies from India have evaluated the prescription pattern of Psychiatrists. Present study was undertaken to analyze the prescription pattern and drug used in psychiatric Out Patients of private practitioners of Central India. Methods: One thousand prescriptions were collected by undergraduate students from chemist and analysed. Study parameter like demographic profile of patients viz. age, sex, diagnosis were recorded. Basic drug indicators, the prescribing pattern of antipsychotics and other categories of drugs were also recorded. The most common and, top brands of anti psychotics were analyzed .Inappropriate prescription if any were recorded and analyzed further. Result: The most common psychotropic drugs were anti-anxiety in 361(36.1%) and antidepressants 130 (13%) prescribed for various psychiatric disorder. Usage of Sedative Hypnotics 104(10.4%), anti-psychotics 90(9%) and anticonvulsants 80 (8%) drugs in prescriptions. The incidence of polypharmacy (22%) was common occurrence in prescriptions. The commonest combination prescribed was of tricyclic antidepressant with benzodiazepines. Central anti-cholinergic was commonly prescribed with anti psychotics. Conclusions: Anti-anxiety drug (benzodiazepines) was the most frequently prescribed class of psychotropic drugs in various psychiatry disorders. The prescribing prevalence of Alprazolam with different brand names was more than that of other benzodiazepines. The combination of different psychotropic drugs were also prescribed.